QTLs associated with resistance to the cassava mosaic disease: new directions for a diverse planet - Lokko, Y.; Gedil, Melaku A; Dixon, A. (2004)
The cassava mosaic disease (CMD) is an economically important disease of the food crop cassava (Manihot esculenta Crantz) in Africa. Quantitative trait loci (QTLs) associated with resistance to CMD were identified using 132 F1 progeny derived from a cross between the CMD resistant accession TMSI30572 and the susceptible landrace TME117. The population was evaluated in the field for two growing seasons in Nigeria. Mean disease severity scores (MDSS) were used for QTL analysis. Five highly significant (p<0.001) marker-associated QTL effects, explaining between 10.47 and 12.15% of the total phenotypic variation, were detected by regression in the old source of resistance. The Kruskal Wallis analysis further detected four highly significant marker-associated QTL effects. Significant marker trait associations were due to markers donated by both parents, which confirms the polygenic and recessive nature of this source of resistance.